Performance and Analysis of Indirect Torque Control-Based Three-Phase Induction Motor - Pradipta, Andri; Triwijaya, Santi; Ridwan, Mohamad (Faculty of Engineering, Universitas Tanjungpura, 2021)
Induction motors are widely used in industrial processes, vehicles and automation. Three-phase induction motors can be used for traction systems on electric locomotives. In this case, the speed control system is an important thing that must be applied to the propulsion system. This study aimed to test the indirect torque control for a Three-phase induction motor. A proportional integral (PI) controller was applied for speed controller. The indirect torque control system was modeled and simulated using PSIM software. According to the result, the control method showed a good performance. The speed could be maintained even the speed reference was changing or a load was applied. The steady state error of the speed response was just 0.1% with rise time around 0.06 s. The stator current went up to 39.5 A in starting condition. The stator current reached 12 A rms when the load of 10 Nm was applied. Then, the current rose to 15.7 A rms when the load was increased to 40 Nm and the current came down to 12.8 A rms when the load was decreased to 20 Nm.